Metabolic disturbances during treatment with second generation antipsychotics - Manusheva, Nensi; Babinkostova, Zoja; Arsova, Slavica; Hadjihamza, Kadri; Naumovska, Andromahi; Markovikj, Snezhana (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2022)
Second generation antipsychotics (SGA) cause side effects through weight gain, dyslipidemias (cholesterolemia, hypertriglyceridemia) as well as affected glucose homeostasis in terms of hyperglycemia,insulin resistance and the incidence of type 2 diabetes mellitus. The aim of this study was to investigate metabolic changes in patients treated with SGA. Materials and methods: This was a prospective study of 50 patients treated with SGA (olanzapine, clozapine, risperidone, quetiapine, aripiprazole) at the PHI University Clinic of Psychiatry who met the relevant ICD-10 criteria. The following parameters were monitored: history and clinical examination, blood pressure and pulse, height, weight, body mass index (BMI), Brief Psychiatric Rating Scale (BPRS), Clinical Global Impression Scale (CGI-S), dose of prescribed SGA,as well as: fasting glycemia, lipid status, HDL, LDL, glycosylated hemoglobin (HgA1C). The parameters were determined at the beginning and after three months of treatment. Results: The subjects in terms of the criteria of metabolic syndrome were: 64% with a larger waist circumference, 53.2% with an increase in systolic and/or diastolic blood pressure, 31.3% with a BMI>30, and 39% with an increase in glycaemia and reduced HDL values ​​at 23.4%. Also,18% of the respondents met three or more criteria. Statistical analysis of the differences in the analyzed parameters showed statistically significant differences for the CGI-S score (p = 0.00007) and for the diastolic pressure (p = 0.038). Correlation of equivalent doses of SGA with BMI (r = -0.637) was obtained. Discussion: The study confirmed presence of metabolic disorders in patients treated with SGA. Although there was no significant difference of metabolic syndrome parameters in relation to the general population, a correlation with BMI has been established. Conclusion: This study showed that patients treated with second-generation antipsychotics should be monitored during their treatment for the parameters of the metabolic syndrome, particularly BMI.
Keywords: metabolic syndrome; second generation antipsychotics; psychiatric disorders